2011
DOI: 10.1177/1352458510391344
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of cladribine tablets in multiple sclerosis: the CLARITY (CLAdRIbine Tablets treating multiple sclerosis orallY) study

Abstract: Background: Cladribine is a synthetic deoxyadenosine analogue in development as an oral multiple sclerosis (MS) therapy. Objective: To report in detail the safety findings from the 96-week, phase III, double-blind CLARITY study, which evaluated treatment with cladribine tablets in relapsing-remitting MS. Methods: A total of 1,326 patients were randomized 1 : 1 : 1 to two short-course regimens of cladribine tablets (3.5 or 5.25 mg/kg cumulative dose over 96 weeks) or placebo. Safety assessments included monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 17 publications
3
113
0
1
Order By: Relevance
“…In a Phase III trial of 1,326 patients that were randomly assigned one of two cumulative doses of cladribine (3.5 mg or 5.25 mg/kg of body weight), cladribine significantly reduced relapse rates, the risk of disability progression, and MRI measures of disease activity at 96 weeks [Giovannoni et al, 2010]. However, because of safety concerns (e.g., lymphocytopenia, herpes zoster infections, and neoplasms including malignancies) were more common in cladribine than placebo recipients [Cook et al, 2011], approval was declined from the EMEA and the FDA, in 2010 and 2011, respectively. Following the FDA ruling, cladribine was withdrawn from the market in both Australia and Russia.…”
Section: Movectro (Cladribine)mentioning
confidence: 95%
“…In a Phase III trial of 1,326 patients that were randomly assigned one of two cumulative doses of cladribine (3.5 mg or 5.25 mg/kg of body weight), cladribine significantly reduced relapse rates, the risk of disability progression, and MRI measures of disease activity at 96 weeks [Giovannoni et al, 2010]. However, because of safety concerns (e.g., lymphocytopenia, herpes zoster infections, and neoplasms including malignancies) were more common in cladribine than placebo recipients [Cook et al, 2011], approval was declined from the EMEA and the FDA, in 2010 and 2011, respectively. Following the FDA ruling, cladribine was withdrawn from the market in both Australia and Russia.…”
Section: Movectro (Cladribine)mentioning
confidence: 95%
“…[41][42][43] Data on cladribine exposure in human pregnancy are limited. 43,44 A successful pregnancy following administration of cladribine to a patient with hairy cell leukemia was reported. 45 It is not known if cladribine crosses the placenta or is secreted in breast milk.…”
Section: Cladribinementioning
confidence: 99%
“…Later, cladribine was tested as an oral agent for RRMS, tablets being taken in two cycles of few days per year [84]. Cladribine for RRMS was tested in the placebo-controlled CLARITY trial and reduced both the frequency and severity of relapses, and suppressing the MRI enhancing lesions at 6 months [87]. The recently reported results of a 120-week extension demonstrated that in a majority of patients, the clinical benefits on relapses and disability as well as on MRI outcome measures of 3.5mg/kg cladribine given in the first two years of the trial can be maintained for at least 4years [88,89].…”
Section: Cladribinementioning
confidence: 99%